Occurrence of Salmonella enterica subsp. enterica in bivalve molluscs and associations with Escherichia coli in molluscs and faecal coliforms in seawater. (February 2018) - Rubini, Silva; Galletti, Giorgio; D'Incau, Mario; Govoni, Guido; Boschetti, Lari; Berardelli, Chiara; Barbieri, Stefania; Merialdi, Giuseppe; Formaglio, Andrea; Guidi, Enrica; Bergamini, Mauro; Piva, Silvia; et al.
Abstract: The objectives of this study were to present data on the presence of Salmonella enterica subsp. enterica and on the enumeration of Escherichia coli and faecal coliforms respectively in different species of bivalve molluscs and seawater and to conduct a retrospective evaluation to assess the capacity of E. coli in molluscs and faecal coliforms and S. enterica subsp. enterica in sea and brackish water to predict the presence of S. enterica subsp. enterica in bivalve molluscs, and therefore, the risk of exposure for consumers. Data were collected from 4972 seawater samples and 5785 live bivalve molluscs samples (2877 Ruditapes philippinarum, 2177 Mytilus galloprovincialis, 256 Chamelae gallina and 475 C. gigas and O. edulis ) collected in the molluscs production area of Ferrara, Northern Italy, from 1997 to 2015. An overall S. enterica subsp. enterica occurrence of 2.2% was reported in water and molluscs, with percentages varying depending on the type of sample and on the classification areas. All the 237 Salmonella strains were identified as genus Salmonella and a total of 53 different serovars were observed. Significant associations between the fecal indicators and presence of S. enterica subsp. enterica were observed both applying EU and USA criteria, but, it should be noted that the EU approach seems to be more stringent achieving the goal of identifying the most critical batches (94 out of the 100) whereas, following the USA approach, a not negligible and higher number of batches compliant for faecal coliforms but contaminated by S. enterica subsp. enterica has to be mentioned. In any case, the faecal indicators E. coli in molluscs and faecal coliforms in seawaters reflect only in part the presence of S. enterica subsp. enterica in molluscs and the consequent potential risk for consumers. Microbiological evaluation of seawaters seems to have a minor impact into the prediction of S. enterica subsp. enterica presence in molluscs. Highlights: The presence of Salmonell a in 10 757 molluscs and water samples was presented. An higher Salmonella prevalence in R. philippinarum has been observed. Faecal indicators reflected only in part the presence of Salmonella in molluscs. Seawaters' analysis seems to not adequately predict Salmonella presence in molluscs.